THE CORRELATION TEST ANXIETY AND SLEEP QUALITY WITH LEARNING CONCENTRATION - Chandra Tri Wahyudi (Fakultas Ilmu kesehatan UPN Veteran Jakarta, 2019)
Nursing students were required to concentrate on the lecture activities. Learning concentration was an important aspect for better result in academic performance. Test anxiety and sleep quality were one of the factors that can influence it. The aim of this study was to analyze correlation between test anxiety and sleep quality with learning concentration of nursing students in UPN “Veteran” Jakarta. This study used descriptive analysis with cross sectional approach. Sampling technique used stratified random sampling with sample amounted to 209 respondents. The results of statistical test chi square was obtained p-value 0,019 (p-value < 0,05), indicated there was significant correlation between test anxiety with learning concentration. The results of statistical test chi square was obtained p-value 1,000 (p-value > 0,05), indicated there was no significant correlation between sleep quality with learning concentration. Learning concentration caused not only by test anxiety and sleep quality, but also caused by environment, psychology, learn modality, and social intercourse. Test anxiety can give positive and negative effects, depends perception of each individual. When it leads to negative effects, stress management was needed to overcome test anxiety. Bad sleep quality can reduce learning concentration. This condition should be addressed by changing sleep patterns in each individual.